2015
DOI: 10.1124/mol.115.102509
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Analysis When There Is a Correlation between Affinity and Efficacy

Abstract: The shape of a concentration-response curve (CRC) is determined by underlying equilibrium constants for agonist binding and receptor conformational change. Typically, agonists are characterized by the empirical CRC parameters efficacy (the maximum response), EC 50 (the concentration that produces a half-maximum response), and the Hill coefficient (the maximum slope of the response). Ligands activate receptors because they bind with higher affinity to the active versus resting conformation, and in skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…In our study, the production of TNF-alpha, TLR4, and CD11c in response to uric acid exhibited a typical dose-response relationship, where a maximum effect is found and, beyond this point, a plateau can be seen, which indicates saturation and the abolishment of the observed effect [47]. The dose-response relationship has been attributed to the interaction between ligand and its receptor [47,48], which suggested to us the possible involvement of a molecule able to transport uric acid inside the macrophage, as is the case of URAT1.…”
Section: Discussionsupporting
confidence: 53%
“…In our study, the production of TNF-alpha, TLR4, and CD11c in response to uric acid exhibited a typical dose-response relationship, where a maximum effect is found and, beyond this point, a plateau can be seen, which indicates saturation and the abolishment of the observed effect [47]. The dose-response relationship has been attributed to the interaction between ligand and its receptor [47,48], which suggested to us the possible involvement of a molecule able to transport uric acid inside the macrophage, as is the case of URAT1.…”
Section: Discussionsupporting
confidence: 53%
“…Fig. 4 (Bottom) shows log-log plots of K d versus E 1 [a "bindinggating" plot (20)] for the agonists at each site (SI Appendix, Eq. S4).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that, on average, hold approximately doubles the agonist's binding free energy. As a consequence, on a log-log scale, there is a linear correlation between K d and E 2 , which is the gating equilibrium constant with two bound agonists (20).…”
Section: Significancementioning
confidence: 99%
“…7 ). Recently, it was suggested that agonist affinity and efficacy might be very tightly related in nicotinic channels 33 . However, our data not only show that this is not the case in AMPA receptors, but provide an intuitive reason why not.…”
Section: Discussionmentioning
confidence: 99%